2020
DOI: 10.31349/revmexfis.66.479
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and degradation kinetics of epoxy-γ-alumina and epoxy-zinc oxide light weight composites

Abstract: Lightweight composite materials are the gold standard in aeronautical and aerospace applications due to their strength and low mass. To carry higher payloads and decrease launching costs, nanosatellites lightweight. Additionally, nanosatellites must also resist high thermal radiation loads while working in orbit. Polymer-based composite materials maintain low mass and added reinforcing ceramic fillers contributes to increasing radiation resistance, thus producing composites that meet both requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk–shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,37–50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk–shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,37–50…”
Section: Resultsmentioning
confidence: 99%
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk-shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] By contrast, g-Al 2 O 3 @C YSMSs have a slightly lower HC of 2.06 W m À1 K À1 (2.4% decrease), which is mainly caused by the phonon scattering at the interface between g-Al 2 O 3 and amorphous carbon, together with the intrinsic low heat/electrical conductance of amorphous carbon with low graphitization (Fig. 7c1).…”
Section: The Thermal Performancementioning
confidence: 99%
“…However, this effect is outside of the scope of the present investigation and is therefore not quantified. In order to characterize the thermal properties of the composite material, thermogravimetric (TGA) and transient thermal response analysis were performed and the thermal conductivity, diffusivity and heat capacity were calculated [27]. In Table 2, the thermal properties of the epoxy resin/ZnO nanoparticles and the carbon fibre are shown, the properties of the carbon fibre were taken from Reference [29].…”
Section: Conceptual Designmentioning
confidence: 99%
“…During the first stage of the project it was found that the addition of nanoparticles increase the resistance to UV radiation with respect to the original composite material [24], this effect has been found for different composite and coatings materials [25,26]. Also, the characterization of this composite demonstrated that the presence of the Zinc Oxide nanoparticles (ZnO) into the polymeric matrix slightly improve its thermal properties [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ZnO treatment has been added to epoxy systems, and the stiffness of the composite undergoes a notable 20% increment [11]. Thermal degradation results show that introducing small percentages of ZnO do not alter the thermal degradation of the epoxy resin as well as the thermal properties are briefly improved [12,13]. These reasons push ZnO to be an alternative filler for the facility of synthetizing, processing an integration on thermoset based composites.…”
Section: Introductionmentioning
confidence: 99%